EFNA4 promotes cell proliferation and tumor metastasis in hepatocellular carcinoma through a PIK3R2/GSK3β/β-catenin positive feedback loop - Junhao Lin; Chunting Zeng; JiaKang Zhang; Zhenghui Song; Na Qi; Xinhui Liu; Ziyan Zhang; Aimin Li; Fengsheng Chen (Elsevier, 2021)
Rapid tumor progression, metastasis, and diagnosis in advanced stages of disease are the main reasons for the short survival time and high mortality rate of patients with hepatocellular carcinoma (HCC). Ephrin A4 (EFNA4), the ligand of the EPH family, participates in the development of blood vessels and epithelium by regulating cell migration and rejection. In our study, based on bioinformatics analyses, we found that EFNA4 was highly expressed and led to poor prognosis in patients with HCC. We demonstrated that overexpression of EFNA4 significantly promoted HCC cell proliferation and migration in vivo or in vitro. In addition, knockdown of EFNA4 inhibited the proliferation and migration of HCC cells. Furthermore, EFNA4 was found to directly interact with EPHA2 and promote its phosphorylation at Ser897, followed by recruitment of phosphoinositide-3-kinase regulatory subunit 2 (PIK3R2) and activation of the glycogen synthase kinase-3beta (GSK3β)/β-catenin signaling pathway. Moreover, overexpression of β-catenin further promoted the expression of PIK3R2, which formed a positive feedback loop. The results revealed that abnormal expression of EFNA4 is the main switch of the PIK3R2/GSK3β/β-catenin loop that influenced the proliferation and migration of HCC cells and suggest that EFNA4 is a potential prognostic marker and a prospective therapeutic target in patients with HCC.